(3GdJNWjW GdGSJQGJjLj (B:s (3eaGgje eYGUQI (B/s - (3GdhdjO, HTGQ jRjOs ((3YeGf(B: s (3OGQ GdQGjI(B, s, 2010)
(3GdGOGQI h GdYedjI GdGOGQjI , GdJNWjW , GdJNWjW GdGSJQGJjLj h GdJNWjW GdeQMdj , , GdJNWjW GdGSJQGJjLj ddeHjYGJ , GdJNWjW GdGSJQGJjLj ddJfejI GdGbJUGOjI (B.s
(3eQGLY U(B.145s
Keywords: (3GdGOGQIs; (3GdJNWjWs; (3GdJNWjW GdEbJUGOjs